Borders, Boundaries, and Exclusion in the Icelandic Asylum System - Tryggvadóttir, Helga Katrín; Skaptadóttir, Unnur Dís (Refuge, 2018)
Grounded in theories of borders and boundaries, this article critically engages with the processes through which asylum seekers in Iceland are excluded from full participation in society. Immigration laws and bureaucratic barriers contribute to this exclusion, which is a result of restrictions on labour market participation, lack of housing, temporality, and lack of meaningful activities. We discuss how borders and boundaries create the identity of the asylum seeker and how the participants in this study experience that identity. We identify three main areas of exclusion: social exclusion, isolation, and cultural boundaries. Fondé sur des théories concernant les frontières et les limites, cet article envisage de manière critique les processus par lesquels les demandeurs d’asile sont, en Islande, exclus d’une pleine participation à la société. Les lois sur l’immigration et les obstacles bureaucratiques contribuent à cette exclusion, qui résulte de restrictions en termes de participationau marché du travail, d’un manque de logements, d’une temporalité et d’un manque d’activités constructives. Nous examinons la manière dont les frontières et les limites créent l’identité du demandeur d’asile, et comment les participants à cette étude vivent cette identité. Nous déterminons par ailleurs trois domaines principaux d’exclusion : l’exclusion sociale, l’isolement et les frontières culturelles.